What works - Cornish, Robert (John Wiley & Sons, Inc., 2012)
What Works provides applicable and relevant info for business owners that you can put to use to help remedy their problems. Authors Robert Cornish and Wil Seabrook offer advice use such as: Know Your Public: Focus all sales and marketing efforts only on companies and people that fit that audience you defined in the profile. This one strategy will dramatically drive growth because you're directing your efforts to the people most likely to do business with you. Measure Weekly: Measuring by week and managing by week can help you avoid a catastrophe that is hard to handle or corr.